Persian lemon in the Mexican counties of Nayarit and Veracruz: Foliar sampling period for nutritional diagnosis - Mellado-Vázquez, Adriana; Salazar-García, Samuel; Hernández-Guerra, Carlos (Revista de Ciencias Agrícolas, 2023)
In Mexico, Nayarit and Veracruz stand out as producers of Persian lemon. Nayarit has a larger surface area with high production potential and a 68% expansion of its cultivated area in the last 10 years. Veracruz has larger planted area and production volume. This investigation was conducted aiming to determine the period of nutritional stability in Persian lemon leaves and define the appropriate time to perform foliar sampling for nutritional diagnosis. In 2017, rainfed orchards were selected in both states. Per orchard, 20 trees were selected, 50 shoots were marked per flow (Nayarit winter and summer, Veracruz winter and spring), and sampled monthly. Soil and foliar nutrient analysis was performed (total nitrogen (N-total) (semi-microKjeldahl digestion), nitrates (NO3) (colorimetry), potassium (K) (atomic absorption), phosphorus (P), sulfur (S), calcium (Ca), magnesium (Mg), copper (Cu), iron (Fe), manganese (Mn), and zinc (Zn), (ICP-Optical Coupled Plasma using an ICAP 7200 spectrophotometer (Thermo Scientific®), and boron (B) (colorimetry) (Genesis 20 spectrophotometer (Thermo Scientific®)). Daily predicted values were calculated and the best functions (highest R2, lowest mean square of the error and value of the Mallows coefficient) were chosen. Mathematical derivatives and criteria were calculated to determine the best period for sampling. For Nayarit, the appropriate period for leaf sampling was the summer flush of July 29 to August 18 and from February 8 to March 19 for the winter flush. In Veracruz, it was from April 10 to May 10 for the winter flush and from September 23 to October 8 for the spring flush.